Tectonic Controls on Late Paleozoic Shale Gas Preservation in Western Shandong, China - Jing Sun; Yuting Zhao; Jie Liang; Xiujuan Zhang; Qingfang Zhao (Journal of Marine Science and Engineering)
Based on structural geology, petrology, shale gas geology, and basin modeling, this study investigates the characteristics of tectonic evolution and sedimentary responses in Western Shandong since the Late Paleozoic. Additionally, this study systematically investigates the hydrocarbon generation and reservoir formation conditions of Late Paleozoic shale gas and analyzes the controlling effects of tectonic activities on shale gas preservation. It is concluded that the TOC of the Late Paleozoic source rocks in this area ranges from 1.0% to 4.5%, considered as moderate to good source rocks. The Ro ranges from 0.7% to 3.5%, indicating a low to overmature stage. Deep concave source rocks have strong hydrocarbon generation potential. The Late Paleozoic shale gas reservoirs in Western Shandong are affected by superposed multiphase tectonic movements, where the activity of fault systems exerts dual controls on shale gas preservation.